Planets - McLure, Kirstie; Couper, Heather; Holroyd, David; Marsh, Stephen ([S.l.] : TLC Video [production company] ; [S.l.] : Discovery Channel Video, 1999)
Scientists and experts around the world discuss what has been learned from the planets and moons of our solar system
Writer, Nigel Henbest ; editor, Raimondo Aiello ; executive producer, Stuart Carter
Narrator: John Hurt
Keywords: Planets; Astronomy